Vietnam : Poverty Reduction Strategy Paper; Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Vietnam has adopted effective policies and measures to accelerate its economic growth rate and reduce poverty while sustaining economic reform, and trying to achieve goals and targets that are set in the Five-year Socio-economic Development Plan 2001-05. The annual progress report, named 'Vietnam, economic growth and poverty reduction' of 2004-05 provides a deeper analysis and evaluation of economic and poverty reduction achievements obtained during the implementation of the Comprehensive Poverty Reduction and Growth Strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet